Effect of short message service as a reminder on breast self-examination in breast cancer patients: a randomized controlled trial*. (April 2015) - Chung, Il Yong; Kang, Eunyoung; Yom, Cha Kyong; Kim, Dongwon; Sun, Young; Hwang, Yoonsun; Jang, Jin Youn; Kim, Sung-Won
Summary: This study was a single-blind randomized controlled trial to assess the effectiveness of SMS as a reminder for breast self-examination (BSE). Participants who underwent surgery for breast cancer were recruited and randomized to the intervention group or the control group. Subjects in the intervention group received one text message on the first day of every month that reminded them to complete monthly BSE and the other text message on the fifteenth day of every month that contained information about breast cancer. Primary and secondary outcomes were self-reported BSE adherence and the frequency of BSE over 6 months. Between August 2010 and December 2011, 216 patients were randomly assigned to the SMS group (n = 110) or the control group (n = 106). A total of 202 patients were included in the final analysis. Self-reported BSE adherence and the frequency of BSE over the past six months were significantly higher in the intervention group than in the control group. Multivariate analysis showed that the SMS was the only significant factor for BSE adherence (p < 0.001). The short-term results of our study suggest that SMS is an effective and low-cost method to enhance adherence to BSE with existing information technology infrastructure.